Solitary Fireflies of Kangkawat Research Station, Imbak Canyon, Sabah - Vickly Mobilim; Mahadimenakbar Mohamed Dawood (2020)
A survey on solitary fireflies was carried out at Kangkawat Research Station in October 2018. A total of 33 fireflies were collected; three adult males, 13 adult females and 17 larvae. Three fireflies species were identified from male specimens, namely Pygoluciola wittmeri, Luciola sp. and most larvae consists of Pyrocoelia sp. This is a new record, mapping the existence of the species in Imbak, hence expanding the geographical knowledge of Pygoluciola, Luciola and Pyrocoelia. There are five morphospecies of unidentified females and three morphospecies of larvae. Three videos of larvae showed an emission of a long glow while the adult female in captivity exhibited single-peaked pulsing light. Male flashes were observed to emit long glows with intermittent rest. Most adult fireflies were caught flying between trees while larvae were found among twigs, leaf litter and leaves.